2000
DOI: 10.1007/pl00000681
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation of cytoplasmic proteins in proliferating, differentiating, apoptotic HL-60 cells and blood neutrophils

Abstract: Two-dimensional electrophoretic analysis was used to assess quantitative and qualitative changes in the expression and tyrosine phosphorylation of cytoplasmic proteins of proliferating, differentiating HL-60 cells and mature human blood neutrophils. The total tyrosine phosphorylation level of cytoplasmic proteins appeared approximately constant during the pre-commitment period, i.e., 6-24 h after induction of differentiation by 700 nM all-trans retinoic acid. At the time of granulocytic phenotype formation (48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Finally, we screened cytosolic and nuclear protein maps in HL‐60 control cells, cells induced to apoptosis, or cells treated with a broad caspase inhibitor. In our previous studies,18 we demonstrated that the synthesis of new proteins and protein modification occur during the induction of HL‐60 cells to granulocytic differentiation. We suggested that changes in protein synthesis and protein tyrosine phosphorylation seen in differentiating HL‐60 cells reflect both the formation of the differentiated granulocyte phenotype and the apoptotic process.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, we screened cytosolic and nuclear protein maps in HL‐60 control cells, cells induced to apoptosis, or cells treated with a broad caspase inhibitor. In our previous studies,18 we demonstrated that the synthesis of new proteins and protein modification occur during the induction of HL‐60 cells to granulocytic differentiation. We suggested that changes in protein synthesis and protein tyrosine phosphorylation seen in differentiating HL‐60 cells reflect both the formation of the differentiated granulocyte phenotype and the apoptotic process.…”
Section: Discussionmentioning
confidence: 87%
“…We also found tyrosine-phosphorylated proteins that were specific to the nucleus of differentiated HL-60 cells; some of these proteins were tyrosine phosphorylated in the cytoplasm before being moved into the nucleus and others were tyrosine phosphorylated after nuclear translocation. We have previously shown (Treigyte et al 2000) that tyrosine phosphorylation of cytosolic proteins increased significantly in HL-60 cells undergoing differentiation. The patterns of nuclear proteins revealed by 2-DE showed that soon after differentiation was induced, the tyrosine phosphorylation level of some proteins increased markedly, especially with acidic and neutral pI, whereas some tyrosine-phosphorylated proteins had undergone dephosphorylation either markedly or completely.…”
Section: Discussionmentioning
confidence: 92%
“…Camptothecin has been shown to induce DNA strand breaks in vivo, and is related to the formation of a camptothecin-induced cleavable topoisomerase-DNA complex [37]. Another factor common to both camptothecin and topoisomerase II inhibitors is that the cytotoxic effects induced by these drugs have been shown to correlate to the degree of tyrosine phosphorylation of cellular proteins other than the topoisomerases themselves [38,48]. Interestingly, we and others have demonstrated previously that neutrophils undergo significant tyrosine phosphorylation when stimulated with fMLP or CPPD crystals [23,49,50].…”
Section: Discussionmentioning
confidence: 99%